2014
DOI: 10.1080/00380768.2014.935695
|View full text |Cite
|
Sign up to set email alerts
|

Sodium (Na+) and silicon (Si) coexistence promotes growth and enhances drought resistance of the succulent xerophyteHaloxylon ammodendron

Abstract: Haloxylon ammodendron (C. A. Mey), a C 4 perennial woody species of the desert areas of northwest China, is a succulent xerophyte that has excellent adaptability to adverse arid environments. Our previous investigations showed that sodium (Na + ) has a positive effect on the growth and drought resistance of Haloxylon ammodendron under drought conditions, which was closely related to high Na + accumulation in photosynthesizing stems (PS). In this study, we further investigated the effect of Na (as sodium chlori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 43 publications
(56 reference statements)
0
23
0
Order By: Relevance
“…Si was shown to reduce impacts Cd stress on mangroves, where the high availability of Si in the sea water could play a key role in the tolerance of heavy metals of mangroves (Zhang et al 2013b). Kang et al (2014) demonstrated a positive impact of Si on the growth of Haloxylon ammodendron, a woody C4 arid-zone species, in drought conditions, but in a complicated association with NaCl. Si contributes to the salt tolerance of the marsh grass Spartina densiflora, despite its other adaptations to salinity and may contribute to the invasive success of this weed (Mateos-Naranjo, Andrades-Moreno & Davy 2013).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Si was shown to reduce impacts Cd stress on mangroves, where the high availability of Si in the sea water could play a key role in the tolerance of heavy metals of mangroves (Zhang et al 2013b). Kang et al (2014) demonstrated a positive impact of Si on the growth of Haloxylon ammodendron, a woody C4 arid-zone species, in drought conditions, but in a complicated association with NaCl. Si contributes to the salt tolerance of the marsh grass Spartina densiflora, despite its other adaptations to salinity and may contribute to the invasive success of this weed (Mateos-Naranjo, Andrades-Moreno & Davy 2013).…”
Section: Discussionmentioning
confidence: 97%
“…Kang et al . () demonstrated a positive impact of Si on the growth of Haloxylon ammodendron , a woody C4 arid‐zone species, in drought conditions, but in a complicated association with NaCl. Si contributes to the salt tolerance of the marsh grass Spartina densiflora , despite its other adaptations to salinity and may contribute to the invasive success of this weed (Mateos‐Naranjo, Andrades‐Moreno & Davy ).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…After 4 weeks, plants were thinned out and five uniform plants were kept, and then plants were divided into three groups: control (C), drought (D) and drought with additional NaCF treatment (D+Na). The amount of fertilizer in each pot culture treatment was calculated as T a = 4×T f (Kang et al 2013(Kang et al , 2014, where T a is the total amount of fertilizer in each pot, and T f is the amount of fertilizer in 1 kg dried soil. The SWC in the C group was maintained at 70% of FWC by irrigating with water during the experimental period.…”
Section: Plant Growth Conditions and Drought Treatments In Pot Experimentioning
confidence: 99%
“…Plants have evolved a variety of morphological and physiological adaptations to resist drought and thus to preserve optimal relative water content in their tissues [12,13]. The accumulation of silicon (Si) in plant tissues can increase plant resistance against various abiotic and biotic constraints, including water shortage [14,15]. The beneficial impact of Si on plant water status during water shortage has been shown for many plant species [15].…”
Section: Introductionmentioning
confidence: 99%